INTEGRASI TEKNOLOGI DIGITAL DALAM PEMBELAJARAN DI ERA INDUSTRI 4.0: Kajian dari Perspektif Pembelajaran Matematika - Susilahudin Putrawangsa; Uswatun Hasanah (Jurnal Tatsqif, 2018)
The recent study intends to describe the roles and the principles of integrating digital technology in education at the 4th Industrial Era. The integrartion is studied from mathematics education perspective. It is concluded that the basic principle of integrating digital technology in mathematics education is that the technology does not diminish students’ conceptual understanding or replace students’ intuitions in doing mathematics. Conversely, the technology is utilized to boost students’ conceptual understanding and maximize the development of students’ intuition in doing mathematics. It is identified that there are three didactical functions of digital technology in mathematics education, such as: (1) Technology for doing mathematics, that is the technology is incorporated as alternative learning media in doing mathematical activities; (2) Technology for practicing skills, that is the technology is utilized as a learning environment to master particular mathematical skills; (3) Technology for developing conceptual understanding, that is the technology is integrated as a learning environment to develop students’ conceptual understanding of specific mathematical concepts. This last didactical function is the most expected of integrating digital technology in mathematics education.